Could artificial intelligence revolutionize the development of nanovectors for gene therapy and mRNA vaccines?. (December 2022) - Hasanzadeh, Akbar; Hamblin, Michael R.; Kiani, Jafar; Noori, Hamid; Hardie, Joseph M.; Karimi, Mahdi; Shafiee, Hadi
Abstract: Gene therapy enables the introduction of nucleic acids like DNA and RNA into host cells, and is expected to revolutionize the treatment of a wide range of diseases. This growth has been further accelerated by the discovery of CRISPR/Cas technology, which allows accurate genomic editing in a broad range of cells and organisms in vitro and in vivo . Despite many advances in gene delivery and the development of various viral and non-viral gene delivery vectors, the lack of highly efficient non-viral systems with low cellular toxicity remains a challenge. The application of cutting-edge technologies such as artificial intelligence (AI) has great potential to find new paradigms to solve this issue. Herein, we review AI and its major subfields including machine learning (ML), neural networks (NNs), expert systems, deep learning (DL), computer vision and robotics. We discuss the potential of AI-based models and algorithms in the design of targeted gene delivery vehicles capable of crossing extracellular and intracellular barriers by viral mimicry strategies. We finally discuss the role of AI in improving the function of CRISPR/Cas systems, developing novel nanobots, and mRNA vaccine carriers. Graphical Abstract: ga1 Highlights: Nucleic acid gene therapy could revolutionize the treatment of many diseases. However, there is still a lack of effective, non-toxic gene delivery systems. Advances in artificial intelligence will improve the design of such systems.